2021
DOI: 10.1093/heapol/czab058
|View full text |Cite
|
Sign up to set email alerts
|

‘I was trying to get there, but I couldn’t’: social norms, vulnerability and lived experiences of home delivery in Mashonaland Central Province, Zimbabwe

Abstract: Increasing facility-based delivery rates is pivotal to reach Sustainable Development Goals to improve skilled attendance at birth and reduce maternal and neonatal mortality in low- and middle-income countries (LMICs). The translation of global health initiatives into national policy and programmes has increased facility-based deliveries in LMICs, but little is known about the impact of such policies on social norms from the perspective of women who continue to deliver at home. This qualitative study explores t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…This cascade of events likely contributed to the two-fold higher risk of stillbirth and neonatal mortality among non-institutional deliveries in our study. This offers a potential explanation for the ndings of a recent study carried out in Zimbabwe which found that women, burdened by multiple interacting vulnerabilities related to poverty, were most likely to deliver 'on the road' whilst attempting to reach a healthcare institution [34].…”
Section: Discussionmentioning
confidence: 98%
“…This cascade of events likely contributed to the two-fold higher risk of stillbirth and neonatal mortality among non-institutional deliveries in our study. This offers a potential explanation for the ndings of a recent study carried out in Zimbabwe which found that women, burdened by multiple interacting vulnerabilities related to poverty, were most likely to deliver 'on the road' whilst attempting to reach a healthcare institution [34].…”
Section: Discussionmentioning
confidence: 98%
“…The women's narratives show how vulnerabilities intersect, including material (food insecurity, available household assets, and access to transportation), social (isolation, distance, and lack of agency for decision-making), and individual-level vulnerabilities (knowledge of signs of labour leading to delays). The women experienced shaming and stigma for delivering at home, making them even more vulnerable to adverse health impacts [13]. The experiences of the women participating in this study illustrate that pursuing progress towards meeting SDG targets at the level of national statistics can lead to negative side effects in some communities, undermining the promise of Agenda 2030 to "leave no one behind".…”
Section: Good Health and Well-beingmentioning
confidence: 92%
“…In the majority of studies, data was collected from extremely poor rural locations or city slums. Not surprisingly, many research participants reported difficulties in accessing health care, including financial barriers, drug shortages and lack of transport [8][9][10][11][12][13]. Six studies also cited shortages of health-care workers and unfriendly interactions with health-care providers as barriers to accessing health care [11,[14][15][16][17][18].…”
Section: Good Health and Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies were quantitative and observational in design [24,[27][28][29][30][31][34][35][36][37][38]. six were qualitative research [26,32,[39][40][41][42], four used mixed-methods design [25,33,43,44], and one was a randomised controlled trial [45]. The details are presented in Table 1 and Fig 2.…”
Section: Vulnerabilities In Maternal Healthmentioning
confidence: 99%